2021
DOI: 10.1016/j.urolonc.2020.11.027
|View full text |Cite
|
Sign up to set email alerts
|

Referral pattern for urologic malignancies before and during the COVID-19 pandemic

Abstract: Introduction The COVID-19 pandemic has required significant restructuring of healthcare with conservation of resources and maintaining social distancing standards. With these new initiatives, it is conceivable that the diagnosis of cancer care may be delayed. We aimed to evaluate differences in patient populations being evaluated for cancer before and during the COVID-19 pandemic. Methods and Materials We performed a retrospective review of our electronic medical record… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 13 publications
0
20
0
Order By: Relevance
“…While Belgium registered high numbers of deaths attributed to COVID-19 (with or without PCR confirmation), excess mortality during the first wave of the COVID-19 pandemic was comparable to average levels for Europe. 26 Despite the varied impact of the pandemic and the diversity of confinement measures to slow the spread of COVID-19 around the world, single-center and multicenter studies, from Italy, 5 , 15 Germany, 13 Austria, 12 Slovenia, 9 Poland, 2 Spain, 11 the UK, 1 and the USA, 3 , 4 , 6 , 14 as well as nationwide, population-level studies from the Netherlands 16 and Denmark, 17 all support a global decline in cancer diagnosis during the early stage of the pandemic. The scarcity of large, population-based studies on cancer diagnoses during the pandemic, to date, is presumably linked to delays in data collection.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While Belgium registered high numbers of deaths attributed to COVID-19 (with or without PCR confirmation), excess mortality during the first wave of the COVID-19 pandemic was comparable to average levels for Europe. 26 Despite the varied impact of the pandemic and the diversity of confinement measures to slow the spread of COVID-19 around the world, single-center and multicenter studies, from Italy, 5 , 15 Germany, 13 Austria, 12 Slovenia, 9 Poland, 2 Spain, 11 the UK, 1 and the USA, 3 , 4 , 6 , 14 as well as nationwide, population-level studies from the Netherlands 16 and Denmark, 17 all support a global decline in cancer diagnosis during the early stage of the pandemic. The scarcity of large, population-based studies on cancer diagnoses during the pandemic, to date, is presumably linked to delays in data collection.…”
Section: Discussionmentioning
confidence: 99%
“…Studies looking at the use of specific diagnostic modalities or first referrals for oncology services alerted to a potential influence of the COVID-19 pandemic on cancer detection. 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 Likewise, single-center and multicenter studies, and population-level studies focused on specific tumor types have reported declines in numbers of cancer diagnoses. 1 , 2 , 7 , 9 , 10 , 11 , 12 , 13 , 14 , 15 Evidence from large-scale studies quantifying these declines on a population level is limited.…”
Section: Introductionmentioning
confidence: 99%
“…Another study including 678 dermatologists surveyed between April and May 2020 showed that daily clinical activity had reduced by more than 75% during the pandemic for almost half of the sample, while approximately 40% of participants reported working fewer days per week compared with before the COVID-19 pandemic (Conforti et al 2021 ). The COVID-19 pandemic not only has resulted in a decrease in the activity of general and specialized practices, but has also impaired the coordination between different types of practices, and this has led to decreased referral for possible cancer diagnoses to specialized practices or hospital departments (Gathani et al 2021 ; Maganty et al 2021 ). Second, patients’ fear and concerns about the COVID-19 might have favored delayed or avoided medical care.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, the urology team of our institution has described a reduction in all urologic activities performed during the first COVID-19 wave in the three largest public hospitals in Lombardy (Brescia, Bergamo and Milan) [ 12 ]. In accordance with recommendations by international urological societies, some urologic oncology surgical procedures have undergone a significant reduction in volume based on specific prioritization strategies, leading to an increased backlog of cases and possibly a worse prognosis for some patients [ 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 ].…”
Section: Introductionmentioning
confidence: 99%